A new genus of Lauxaniidae (Diptera) from New Caledonia - Gaimari, Stephen D. (Zootaxa, 2004)
The new genus Evertomyia (Diptera: Lauxaniidae) from New Caledonia is described and illustrated, along with six new species, albeto, frankadelia, irwini, helenae, matilei and webbi. Phylogenetic relationships among the six species are hypothesized, character states are discussed, and a key to the genus and its species is provided.